MENGUJI PENGARUH KUALITAS PRODUK, STORE ATMOSPHERE, DAN HARGA TERHADAP LOYALITAS PELANGGAN DI WEDANGAN SELARAS - nabela novelia16 (JURNAL WIRANOMIKA, 2026)
Abstract: This study aims to examine the influence of product quality, store atmosphere, and price on customer loyalty at Wedangan Selaras. This study used a survey method. Data were collected through questionnaires distributed to 100 respondents who were Wedangan Selaras customers. This analysis used SPSS. The coefficient of determination value shows that customer loyalty is influenced by the third variable by 37.2%.   Keywords : product quality; store atmosphere; price; customer loyalty.